Morphology, Nest Characters, and Behavior: Taxonomic Aids in Facilitating Identification of Tetragonula biroi Friese (Hymenoptera: Apidae: Meliponini) - Nicolas, Amelia (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2023)
Tetragonula biroi Friese, the most popular stingless bee species in the Philippines, belongs to Tetragonula, a difficult genus to deal with due to the high character variability of workers. This paper provides a detailed description of the morphological characters, nest features, and behavioral characteristics of T. biroi to help facilitate its classification and identification. Proper identification of stingless bees is crucial in biodiversity conservation, genetic improvement, and pest management.